Seleção de habitat de Myrmotherula snowi Teixeira & Gonzaga, 1985 (Aves, Thamnophilidae), uma espécie criticamente ameaçada de extinção - Vilela, Hermínio Alfredo Leite Silva (2020)
Habitat selection is the process of disproportionately using the habitat, which involves the trade-off between the benefits and costs for the individual. Some factors can influence this process, such as intrinsic population issues, environmental variations, vegetation structure and food availability. In this way, understanding the individual-habitat relationship can be fundamental to save threatened species. In this scenario, the Alagoas Antwren (Myrmotherula snowi), a critically endangered bird at the global level, with a population restricted to Murici-AL and with fewer than 40 individuals, was the subject of a study to test the hypothesis that reduced interspecific competition would be sufficient for the most suitable habitats to be selected. Additionally, we checked if there is another bird bioindicator of the same types of habitats as M. snowi. The data collection occurred in the Murici Ecological Station, a Dense Ombrophilous Forest, where 28 sites with eight characteristics that may be related to the occupation of M. snowi were selected. During the months of October to March 2018-19 and 2019- 20, at each site, we checked the presence of M. snowi and the local avifauna. The Mark program was used to generate 256 single-season occupancy models with the eight variables to verify the best indicators of M. snowi occupation. To identify if any bird species can be a bioindicator of the sites occupied by M. snowi, the Indicator Value statistical test was performed. In total, 17 individuals of M. snowi were observed in nine sites, the detections were predominant in the months of October to December and the best model was the one that considered the average height of the trees, distance to the stream and slope. Trogon muriciensis was a species indicator of the same habitats as M. snowi. Our data support the idea that M. snowi occupies habitats that have at least three important characteristics, with the average height of the trees being a more decisive factor in site selection. We highlight that the highest chance of detecting the bird in the last months of the year may be associated with territory defense that coincides with the beginning of the dry period. Probably the non-occupation of suitable sites is related to the reduced population and that intrinsic population factors may be preventing its growth, for this reason, we consider it urgent to understand these causes that prevent the occupation of these suitable habitats. In addition, it is necessary to make priority searches for the bird in other locations between the months of October to December, with special attention to regions that present an advanced conservation aspect of the vegetation, as well as to places close to stream and with low slope, noting also the eventual presence of T. muriciensis in the region. In this way, the best sites for eventual captive breeding and release of individuals. These information can bring light to subsidize conservation and management strategies of M. snowi.